Effects of diacetyl-liensinine on electrophysiology in rabbit ventricular myocytes - Feng Cao; Teng Wang; Wenmao Ding; Zhe Li; Shaobo Shi; Xiaozhan Wang (BMC, 2017)
Abstract Background Diacetyl-liensinine is a chemosynthetic derivative of liensinine, extracted from the seed embryo of Nelumbo nucifera Gaertn, in China. It has been found to have extensive anti- arrhythmic actions. The present study was designed to investigate the effects of diacetyl-liensinine on electro- physiology of myocytes. Methods We exposed rabbit ventricular myocytes to diacetyl-liensinine using standard whole-cell patch-clamp technique and measured the action potential, L-type calcium current (I Ca-L), delayed rectifier potassium current (I K), transient outward potassium current (I to) and inward rectifier potassium current (I K1). Results Our results showed that diacetyl-liensinine significantly prolonged action potential duration at 50 and 90% repolarization (APD50, APD90), at 10 and 30 μM, while shortened APD50 and APD90 at 100 μM. In addition, diacetyl-liensinine inhibited the ICa-L, IK, I to and IK1 in a concentration-dependent manner. Conclusions The results suggest that diacetyl-liensinine might be a potential anti-arrhythmic agent.